THERAPEUTIC OUTCOME OF MINIMUM INVASIVE TECHNIQUE FOR ANTERIOR ESTHETICS: CASE REPORT (The Research of Medical Science Review, 2024)
Resin infiltration is one of the minimum invasive procedures. Demineralized enamel hasporosities and is prone to caries. Resin infiltration improves and strengthens thedemineralized enamel and improves the esthetics.